Reinigungsfähigkeit von Filtermedien mithilfe kontinuierlicher und pulsierender Strömung - Weidemann, Caroline (KIT Scientific Publishing, 2014)
This work deals with the analysis of the cleaning mechanism of polymer woven filter media. It reports parametric studies for the cleaning of filter media using continuous and pulsed flows for different kinds of impurities and filter geometries. There the focus is on the development of dimensionless operation numbers, which can be used to predict the cleaning result of the respective filter medium.